THE COMPARISON BETWEEN THE JUDICIAL COMMISSION OF THE REPUBLIC OF INDONESIA AND THE NETHERLANDS COUNCIL FOR THE JUDICIARY - Suparto Suparto (Universitas Kuningan, 2019)
The purpose of this study is to analyze the position and authority of the Judicial Commission of the Republic of Indonesia and its comparison to the Netherlands Council for the Judiciary. This comparative study applied a normative juridical method. The data used in this study were secondary data. The collected data were then analyzed qualitatively. The results showed that Judicial Commission has an important position in judicial system in Indonesia so as structurally, its position is aligned with the Supreme Court and the Constitutional Court of the Republic of Indonesia. Yet, functionally, its role is auxiliary to the judicial power institutions. Although the function of the Judicial Commission is related to judicial power, but the Judicial Commission is not an agent of judicial power, rather, it is an agency enforcing code of ethics of judges. Besides, the Judicial Commission is also not involved in the organization, personnel, administration and financial matters of judges. This condition is different from the Judicial Commission in European countries, such as the Netherlands. The Judicial Commission in the Netherlands (The Netherlands Council for the Judiciary) has an authority in the area of technical policy and policy making in the field of justice. The Netherlands Council for the Judiciary and other Judicial Commission in European countries generally have the authority in managing organization, budget and administration as well as in conducting promotions, transfers, and recruitments as well as imposing sanctions on judges. Thus, the Supreme Court only focuses on carrying out judicial functions and does not deal with administrative and judicial organization matters. Tujuan dari penelitian ini adalah untuk mengetahui dan memahami tentang kedudukan dan kewenangan Komisi Yudisial Republik Indonesia serta perbandingannya dengan Komisi Yudisial Belanda. Metode penelitian yang digunakan yaitu yuridis normatif dengan cara perbandingan (komparatif). Data yang digunakan adalah data sekunder sedangkan analisis data dilakukan secara kualitatif. Hasil penelitian yaitu bahwa kedudukan Komisi Yudisial sangat penting, sehinggasecara struktural kedudukannya diposisikan sederajat dengan Mahkamah Agung dan Mahkamah Konstitusi. Namun demikian secara fungsionalperannya bersifat penunjang (auxiliary) terhadap lembaga kekuasaan kehakiman. Komisi Yudisial meskipun fungsinya terkait dengan kekuasaan kehakiman tetapi bukan pelaku kekuasaan kehakiman, melainkan lembaga penegak norma etik (code of ethics) dari hakim. Selain itu Komisi Yudisial juga tidak terlibat dalam hal organisasi, personalia, administrasi dan keuangan para hakim. Hal ini berbeda dengan Komisi Yudisial yang ada di negara Eropa misalnya Belanda. Komisi Yudisial di Belanda (Netherland Council for Judiciary) memiliki kewenangan pada area kebijakan teknis dan pembuatan kebijakan pada bidang peradilan.Komisi Yudisial Belanda dan di Eropa pada umumnya mempunyai kewenangan dalam hal mengelola organisasi, anggaran dan administrasi peradilan termasuk dalam melakukan promosi, mutasi, rekruitmen dan memberikan sanksi terhadap hakim. Mahkamah Agung hanya fokus melaksanakan fungsi peradilan yaitu mengadili